2015
DOI: 10.4166/kjg.2015.66.2.75
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3Methylation, Loss of RUNX3 Expression and Clinicopathologic Findings according toHelicobacter pyloriCagA in Gastric Carcinoma

Abstract: Background/Aims: Helicobacter pylori cytotoxin-associated gene A (CagA) has been suggested to be involved in the inactivation of Runt-related transcription factor 3 (RUNX3), a known gastric carcinoma tumor suppressor gene. It remains unclear how H. pylori CagA initiates or maintains RUNX3 promoter methylation and inactivates its protein expression in gastric carcinoma. Methods: RUNX3 promoter methylation status, RUNX3 expression, and H. pylori CagA were investigated in 76 sample pairs of gastric carcinoma tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Next, we identified tumour‐suppressive transcriptional factor RUNX3 could regulate expression levels of SIRT1 in gastric cells. It has been revealed that H. pylori infection can inhibit expression of RUNX3 at mRNA levels through CpG island methylation or Src/MEK/ERK and p38 MAPK pathways 41,42 . Work from Tsang et al even showed that H. pylori CagA targets RUNX3 for proteasome‐mediated degradation 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we identified tumour‐suppressive transcriptional factor RUNX3 could regulate expression levels of SIRT1 in gastric cells. It has been revealed that H. pylori infection can inhibit expression of RUNX3 at mRNA levels through CpG island methylation or Src/MEK/ERK and p38 MAPK pathways 41,42 . Work from Tsang et al even showed that H. pylori CagA targets RUNX3 for proteasome‐mediated degradation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that H. pylori infection can inhibit expression of RUNX3 at mRNA levels through CpG island methylation or Src/MEK/ERK and p38 MAPK pathways. 41,42 Work from Tsang et al even showed that H. pylori CagA targets RUNX3 for proteasomemediated degradation. 43 The cytoplasmic mislocation of RUNX3 induced by H. pylori infection can also suppress transcriptional activities of RUNX3.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of CagA into the cytoplasm of the host cell has been shown to play a vital role in H. pylori pathogenesis and GC progression [ 120 , 121 ]. Na et al [ 122 ] reported that patients with poorly differentiated adenocarcinoma and signet ring cell carcinoma of individuals with early GC (EGC) and H. pylori CagA-positive infection exhibited an enhanced methylation of Runt-related transcription factor 3. Simán et al [ 123 ] also drew the conclusion that H. pylori CagA-positive infection is a risk factor of non-cardia gastric adenocarcinoma.…”
Section: Exosomal Proteins Involved In Gc Progressionmentioning
confidence: 99%